Evaluation of hemodynamic response function during mental arithmetic task in fNIRS data using GLM method - Barahimi, Shekoufe; Einalou, Zahra; Dadgostar, Mehrdad (Neuroscience informatics, 2021)
•The regions activated in the brain cortex during mental arithmetic task included the frontal lobe and the parietal lobe.•GLM provides the standard linear estimate of the hemodynamic response to take advantage of the temporal resolution.•The analysis of fNIRS data could practically fill the experimental gaps related to the demonstration of neural performance.•The frontal lobe (DLPFC) and the parietal lobe (left SPL)) act as an active area during the subtraction operations. To understand the complex structure of neural networks in the brain, which is a critical concept in Neuroscience, it is essential to identify different areas of the brain. Studies on the performance of various brain regions and their processing techniques have helped collect a large amount of data about the functions of these areas, which can provide deeper insights into the mechanism of this system. In line with this, the present study seeks to evaluate the hemodynamic response function (HRF) of the cerebral cortex in 8 healthy subjects (3 males and 5 females) during mental arithmetic task (Subtraction of single-digit numbers by two-digit numbers). This is conducted by data recording using functional near-infrared spectroscopy (fNIRS) with 52 channels to identify the active parts of their brain. Following the task (3 or 4 runs), we recorded the brain channel signals of the subjects, removing the noise from the extracted signals using wavelet transform technique. Then, the location of the channels and the active areas of the brain were identified in each individual and the group levels using e general linear model (GLM) method. The findings suggest that at the individual level, dorsolateral prefrontal cortex (DLPFC), supramarginal gyrus (SMG), left superior parietal lobule (left SPL), and right inferior frontal gyrus are activated during the mental arithmetic task (subtraction). Also, at the group level, the frontal lobe (dorsolateral prefrontal cortex (DLPFC)) and the parietal lobe (left superior parietal lobule (left SPL) are activated, which is compatible with brain activation during mental arithmetic task.